A | B |

a + (b + c) = a + (c + b) | associative property of addition |

(-6)(1) = -6 | identity property of multiplication |

a * ( b * 3 ) = ( a * b ) * 3 | associative property of multiplication |

b + 0 = b | identity property of addition |

2 + -2 = 0 | inverse property of addition |

x + 5 = 1x + 5 | identity property of multiplication |

5 + (2m + 3x ) = 5 + ( 3x + 2m ) | commutative property of addition |

-8 * 0 = 0 | zero product property |

3 ( 5x ) = ( 3 * 5 ) x | associative property of multiplication |

9(3 * 2) = (3 * 2)9 | commutative property of multiplication |

-4 (-5 * 6) = -4 ( 6 * -5) | commutative property of multiplication |

8x + -8x = 0 | identity property of addition |

3x + 9 + -8x = 3x + -8x + 9 | commutative property of addition |

2/3 * 3/2 = 1 | inverse property of multiplication |

-3 * -1/3 = 1 | inverse property of multiplication |

5 + ( 2 + 8y) = (5 + 2) + 8y | associative property of addition |